Studies on Cytochrome P450 4X1 - Al-Anizy, Mohammed (2005)
Antisera raised against recombinant human CYP4Z1 (4Z1), mouse Aryl hydrocarbon receptor (AhR), and C.elegans Latrophilin (LpH) proteins were titred over the course of several bleeds. The sensitivity of the antibodies shows an increase over the course of several immunizations, with the minimum amount detected being 1 ng of 4Z1, 0.3 ng of AhR, and 0.3 ng of LpH. Terminal bleeds were taken for the AhR and LpH antisera. The AhR antisera detects proteins in rat and mouse liver cytosol consistent with previous reports of the AhR. LpH is predicted to be localized in a membrane compartment on the basis of its primary structure, so sub-cellular fractions of C.elegans were isolated and tested, revealing a protein of ~113 kDa in a crude membrane preparation. This protein was not solubilized in < 1% Emulgen 913, but was soluble in 2% dodecylmaltoside. A fresh 15k supernatant treated with 2% dodecylmaltoside showed a strong band of LpH protein at ~113 kDa. However, 66 kDa band was detected when the samples were stored overnight at 4 degrees centigrade due to presence of a G protein coupled receptor proteolysis site (GPS) between position M536 and C547 of LpH, which is a characteristic feature in the LpH protein family. In order to study the expression of the CYP 4X1 in mouse tissues, RNase protection assays were performed. Different tissues were assayed at the same time and the same riboprobe was used to hybridise all the samples. The CYP 4\x1 probe was shown to be full length (-ve control). However, the +ve control (RNase positive) shows an absence of signal when hybridised to the yeast tRNA demonstrating the specificity of the signal in the samples. Several RNA samples were hybridised with mouse cyp4X1 gene probe, such as aorta, brain and heart and liver. The mouse cyp4X1 gene appears to have 12 exon from the genomic sequence and encodes a protein which high identity with the human and rat cyp4X1 gene. The full-length of the probe was 424 b.p and the protected fragments were 177 b.p. The murine cyp4X1 was not expressed in control liver, but is expressed in brain at high level. Cyp4X1 gene was also investigated in aorta tissue and found to be expressed at low levels. Known inducers of hepatic cytochrome P450 were used (Ciprofibrate, TCDD, PB, and dexamethasone), but had no induction effect in the samples. Western blotting of brain confirmed that the cyp4X1 protein is expressed in brain, and quantification showed that this is a major cytochrome P450 in brain.